2015
DOI: 10.1590/s1806-37132015000100006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia increases encoding pigment epithelium-derived factor gene expression, although not that of the protein itself, in the temporal cortex of rats,

Abstract: Objective: Obstructive sleep apnea syndrome is mainly characterized by intermittent hypoxia (IH) during sleep, being associated with several complications. Exposure to IH is the most widely used animal model of sleep apnea, short-term IH exposure resulting in cognitive and neuronal impairment. Pigment epithelium-derived factor (PEDF) is a hypoxia-sensitive factor acting as a neurotrophic, neuroprotective, and antiangiogenic agent. Our study analyzed performance on learning and cognitive tasks, as well as PEDF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It should be noted that these prior studies in which CIH induced spatial learning and memory impairments and anxiety-like behaviors were conducted with different CIH protocols (AHI ranged from 40-60) [47,52,[54][55][56][57][58] compared to our CIH protocol (AHI = 10). Indeed, a study using a CIH protocol with an AHI of 20 found no effect of CIH on spatial learning and memory in male rats [110], and another study using an AHI of 15 found no effects on anxiety-like behavior in the open eld in male and female mice [59]. These ndings indicate that CIH protocols with > 20 AHI is necessary to induce spatial learning and memory impairments and anxiety-like behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…It should be noted that these prior studies in which CIH induced spatial learning and memory impairments and anxiety-like behaviors were conducted with different CIH protocols (AHI ranged from 40-60) [47,52,[54][55][56][57][58] compared to our CIH protocol (AHI = 10). Indeed, a study using a CIH protocol with an AHI of 20 found no effect of CIH on spatial learning and memory in male rats [110], and another study using an AHI of 15 found no effects on anxiety-like behavior in the open eld in male and female mice [59]. These ndings indicate that CIH protocols with > 20 AHI is necessary to induce spatial learning and memory impairments and anxiety-like behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…It should be noted that these prior studies in which CIH induced spatial learning and memory impairments and anxiety-like behaviors were conducted with different CIH protocols (AHI ranged from 40 to 60) [ 53 , 58 , 60 64 ] compared to our CIH protocol (AHI = 10). Indeed, a study using a CIH protocol with an AHI of 20 found no effect of CIH on spatial learning and memory in male rats [ 133 ], and another study using an AHI of 15 found no effects on anxiety-like behavior in the open field in male and female mice [ 66 ]. These findings indicate that CIH protocols with > 20 AHI is necessary to induce spatial learning and memory impairments and anxiety-like behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in previous animal studies, postnatal hyperoxic/hypoxemic exposure diminished peripheral chemoreceptors functions, and hypoxic ventilatory responses. Such an effects in early life contribute to lifelong alteration in respiratory control (53)(54)(55)(56).…”
Section: Respiratory Instability: Sleep-disordered Breathingmentioning
confidence: 99%